A Study on the Application of Interpreting Note-taking in College English Teaching - Hu Yingli; Zhang Yue (SHS Web of Conferences)
College English is a core course for undergraduates and a foundation for students preparing for further study. This paper explores the use of interpreting note-taking in college English teaching, aiming to identify effective teaching strategies for practical language instruction. As a method to improve listening and speaking skills, interpreting note-taking enhances students' overall language proficiency. The paper introduces these techniques into classroom practice and discusses their impact, showing improvements in spoken English, especially in integrating and processing linguistic information. However, challenges remain in its implementation.